Molecular Epidemiology of Pathogenic Hantaviruses in the Far East of Russia, 2015-2018 - L. N. Yashina; N. A. Smetannikova; G. G. Kompanets; N. I. Zdanovskaya; L. I. Ivanov (Проблемы особо опасных инфекций, 2020)
Human pathogenic hantaviruses, belonging to the family Hantaviridae, genus Orthohantavirus, are disseminated worldwide and cause hemorrhagic fever with renal syndrome (HFRS) in Europe and Asia. In the Far East of Russia Hantaan (HTNV), Amur (AMRV) and Seoul (SEOV) viruses are etiologic agent of HFRS, while the human pathogenic potential of other seven hantaviruses, circulating in this region, has not been researched adequately yet. Objective of the study was genetic identification of hantaviruses, associated with HFRS in the Far East of Russia during 2015-2018. Materials and methods. Blood samples of 64 HFRS patients from Jewish Autonomous Region, Khabarovsk and Primorsky Territories were analyzed for hantavirus RNA using reverse transcription polymerase chain reaction. Results and discussion. A total of 19 viral RNA isolates from HFRS patients were genetically typed. Etiologic agents of HFRS were three pathogenic hantaviruses: HTNV (13 isolates), AMRV (3 isolates), SEOV (3 isolates). Three genetic lineages were identified among HTNV, two lineages among AMRV One genetic variant of SEOV virus was identified among HFRS patients, which was more close to the strains from South-Eastern Asia than to those from the neighboring countries.